Occupational Hazards of Surgical Smoke and Achieving a Smoke Free Operating Room Environment: Asia-Pacific Consensus Statement on Practice Recommendations - Heroor, Anil Ashok; Asaf, Belal Bin; Deo, Suryanarayana S. V.; Lau, Eric Hui-Lun; Mok, Chi Wei; DiPasco, Peter Joseph; Jain, Pradeep; Anand, Utpal (Frontiers in Public Health, 2022)
Background: Surgical smoke generated through energy devices may present detrimental effects on individuals present in the operating room (OR). Despite the concerns possibly associated with surgical smoke, there may be no mandatory policies that suggest protective measures and limited firm standards are committed yet to address the same. Aim The aim of this paper is to present recommendations for surgeons and OR personnel by taking a consensus approach based on available literature and its interpretation by a multi-national panel of experts. Methods The Asia-Pacific (APAC) group was established with the aims of reviewing literature evidence, discussing key issues regarding surgical smoke and its hazards, and offering a summary of statements in achieving a smoke-free OR environment. Eleven expert surgeons from the international APAC region were gathered with the purpose of coming to a consensus on engineering, best work-practices, and administrative controls in minimizing surgical smoke exposure. A two-phase consensus method was used to obtain opinions from the expert panel of specialists. Statements with an agreement of more than 80% were accepted. Findings For twenty-one statements, the panel achieved consensus on 17 statements; another 5 were dropped due to lack of consensus. The consensus was obtained on statements that address the need for the implementation of administrative policies, training and awareness, standard procedure for the continued use of engineering controls, stringent work practice controls and preventive controls. Conclusion The statements presented may guide surgeons and OR personnel in the practical management of surgical smoke safety, mitigating the risks associated with it. The consensus statement also provides a series of recommendations that can be used with other stakeholders, such as policymakers, hospital administrators and professional societies, to highlight and motivate the implementation of meaningful policies.